How J.P. Morgan picked the winners and losers in the Panic of 1907: An exploration of the individual over the institution as lender of last resort - Jon R. Moen; Mary Tone Rodgers (Essays in Economic & Business History (EEBH), 2022)
The actions taken by J. P. Morgan during the Panic of 1907 reveal how a skilled leader can dominate those of formal institutions during the resolution of a financial crisis. First, we examine how Morgan coordinated emergency liquidity infusions during the Panic in the absence of a formal lender of last resort (LOLR). Morgan's Syndicate Books provide evidence that all applicants for liquidity had participated in earlier bond underwriting syndicates with Morgan. The single denial of aid was to an agent from an unprofitable syndicate, the Knickerbocker Trust. Morgan's decisions to provide or withhold aid to distressed institutions appear to track more closely with his previous syndicate experience with each applicant. Recommendations made by committees he formed to estimate applicants' solvency appear less important. Then, we show that Morgan's decisions had a distinguishable effect during the Panic on the prices of bonds underwritten by his syndicates. We find that during the Panic bond traders revised upwardtheir valuation of bonds underwritten by Morgan compared to bonds underwritten by bankers that had not undertaken LOLR activities. We interpret these results as implying that market agents had greater expectations of valuable advice or liquidity infusions to Morgan-backed issuers than to issuers backed by other bankers. These findings provide support for Morgan's effectiveness as a mobilizer of private reserves, a private LOLR, during the Panic of 1907.
Keywords: G01; G12; G23; G24; L14; N11; N21; 330; JP Morgan; Panic of 1907; lender of last resort; syndicates; liquidity; call loan; clearing house; consols; Knickerbocker Trust; railroad bonds